Maritime Piracy in South-East Asia: the Regional Aspect - Oleg Paramonov (Международная аналитика)
Nowadays maritime piracy is one of the most serious non-traditional security challenges. After significant progress in the fight against maritime piracy in Somalia waters, the situation with maritime piracy and maritime terrorism in South-East Asia once again became the focus of attention of not only regional powers, but also extra-regional actors. At the same time, the ASEAN members States have consistently opposed the internationalization of the South-East Asia maritime piracy problem considering the situation from the point of view of protecting their own sovereignty. However, the regional states themselves do not have sufficient capacity to effectively counter maritime piracy, despite some successes in this field.